Morphoregression and length-weight relationship of Bali sardinella, Sardinella lemuru Bleeker 1853 in Bali Strait Waters - Nyoman Dati Pertami; M.F. Rahardjo; Ario Damar; I.W. Nurjaya (Jurnal Iktiologi Indonesia, 2018)
Bali Sardinella, Sardinella lemuru Bleeker 1853, included in small pelagic groups which have an important economic value. The production of Bali Sardinella was the highest among the other small pelagic fish in Bali Strait waters. The morphoregression and length-weight relationship are important to be known to facilitate the conversion between a length measurement to another type of length measurement and the weight. The aims of this research were to reveal the relationship between total length (TL) and standard length (SL), total length and fork length (FL), fork length and standard length, and the length-weight. The research was held in Bali Strait waters from March 2017 – Mei 2018. The morphoregression was analyzed using simple linear regression, whereas the length-weight relationship using power regression. A total of 470 individuals of Bali sardinella were collected during the study period. The fish that analyzed have a length range 9.7 –20.2 cm TL. The average length of Bali sardinella was13.7 cm. The relationship between total length (TL) and standard length (SL); total length (TL) and fork length (FL); fork length (FL) and standard length (SL) for Bali sardinella respectively were TL = 1.1038SL + 0.9313; TL = 1.0861FL + 0.2967; and FL = 1.0068SL + 0.6936, respectively. The value of b which were generated from the length-weight relationship of Bali Sardinella was 3.22 with the growth patterns were positive allometric. Abstrak Ikan lemuru, Sardinella lemuru Bleeker 1853, termasuk dalam kelompok ikan pelagis kecil yang bernilai ekonomis tinggi. Dibandingkan dengan jenis pelagis kecil lainnya, hasil tangkapan ikan lemuru lebih dominan di perairan Selat Bali. Persamaan morforegresi dan hubungan panjang bobot penting untuk diketahui sehingga mudah melakukan kon-versi dari satu jenis panjang ke jenis panjang lain dan bobotnya. Penelitian ini bertujuan untuk mengungkap hubungan antara panjang total (PT) dengan panjang baku (PB), panjang total dengan panjang cagak (PC), panjang cagak dengan panjang baku, serta hubungan panjang bobot ikan lemuru. Penelitian dilaksanakan di perairan Selat Bali kurun waktu Maret 2017 – Mei 2018. Morforegresi dianalisis menggunakan regresi linear sederhana, sedangkan hubungan panjang bobot dianalisis menggunakan regresi power. Ikan lemuru (Sardinella lemuru Bleeker 1853) yang dikumpulkan selama penelitian berjumlah 470 ekor. Ikan yang dianalisis memiliki kisaran panjang antara 9,7 – 20,2 cm PT. Panjang rata-rata ikan lemuru adalah 13,7 cm. Hubungan antara panjang total (PT) dan panjang baku (PB); panjang total (PT) dan pan-jang cagak (PC); panjang cagak (PC) dan panjang baku (PB) ikan lemuru secara berturut-turut adalah PT = 1,1038 PB + 0,9313; PT = 1,0861 PC + 0,2967; and PC = 1,0068 PB + 0,6936. Nilai b yang terbentuk pada hubungan panjang bobot ikan lemuru adalah 3,22 dengan pola pertumbuhan adalah allometrik positif.